Indigenous Peoples, settler colonialism, and access to health care in rural and northern Ontario. (November 2020) - Burnett, Kristin; Sanders, Chris; Halperin, Donna; Halperin, Scott
Abstract: In Canada rural and northern communities, particularly Indigenous communities, face challenges disproportionate to their urban counterparts in accessing health care services. Existing health research on rural communities has tended to emphasize and reinforce the rural/urban dichotomy in access to and delivery of services, leaving the notion of "rural" as an under-interrogated concept. Drawing on a qualitative study of health care providers, community members, and Indigenous Elders, we explore Indigenous people's beliefs about vaccination to complicate notions of rurality in order to illuminate the ways in which space and settler colonialism both shape and limit choices around health care access. Highlights: Relationships between Indigenous peoples health care providers play an essential role in health care decisions. The history of health care provision and settler colonialism in Canada informs current relationships with Indigenous Peoples. Definitions of rural need to include the impact of how social identities, settler colonialism, and racism operate in those spaces.